Supply Chain Design for Senior Tourists in the Lanna Region of Thailand - Korawan Sangkakorn; Parnhathai Pipithapan; Benjenop Buranasiri; Pairach Piboonrungroj (International Journal of Supply Chain Management, 2016)
Tourism is considered an important sector of the world economy nowadays since this industry is a major source of income for many countries including Thailand. The senior tourist market is an interesting tourism market since the market tends to expand continually due to the worlds senior population growth. Moreover, this elderly market is a potential market with high purchasing power and free time for travelling. Therefore, Thailand should prepare readiness to support this emerging market because it could be another major source of export income. The readiness of tourism management and provision of tourism facilities for senior tourists should be taken into consideration. This paper aims to study the supply chain design for senior tourist and mainly focus on the upper Northern area of Thailand (Lanna region) which has tourism resources and services required for senior tourists demand.